OPTIMALISASI RUTE WISATA DI YOGYAKARTA MENGGUNAKAN METODE TRAVELLING SALESMAN PERSON DAN ALGORITMA BRUTE FORCE - Condro Wibawa (Asosiasi Dosen Muda Indonesia, 2022)
Yogyakarta is one of the popular tourist destinations in Indonesia. There are many tourist sites that can be visited in the city of Yogyakarta, including Prambanan Temple, Breksi Cliff, Van den Berg Museum, and Malioboro. For tourists who are not familiar with these tourist sites, determining the route to be visited is important because it will affect travel costs, especially transportation costs. To solve this problem, the Traveling Salesman Person method and the Brute Force Algorithm are used. The Brute Force algorithm was chosen because of its simple characteristics so that it is easy for all people to understand. The results of the research resulted in the most optimal route with a total cost of Rp. 100,300.00 and the least optimal route with a total cost of Rp. 131,000.00.